A study on the failure of breast feeding during the first month of life with effect on immunological level - Datta, Shyamali; Datta, Bijan Kumar; Banik, Avirupa Kansha; Datta, Nilanjan (International Journal of Contemporary Pediatrics, 2018)
Background: In the critical phase of immunological immaturity of the newborn, particularly for the immune system of mucous membranes, infants receive large amounts of bioactive components through colostrum and breast milk. Breastfeeding provides unsurpassed natural nutrition to the newborn and infant. Study was done to know the effects of breast milk feeding versus formula feeding in early infancy on the development of serum IgA, IgM and IgG. Methods: The present study investigated 100 cases of failure of breast feeding. The cases included both complete and partial failure. Values of immunoglobulin levels (IgA, IgM and IgG) in the serum of eleven breast fed and eleven artificially fed infants (all aged one month) were determined using Tripartigen plates. Results: Mean level of IgA in artificially fed infants was 20.72±3.82µg/100 ml. The diameter of precipitin ring using sample number 7 was 3.9 mm. The mean level of IgA in breast fed infants was 25.94±3.89 µg/100 ml. The mean level of IgM in artificially fed infants was 31.690±3.504 µg/100 ml. The mean level of IgM in breast fed infants was 36.81±5.13 µg/100 ml. The mean level of IgG in artificially fed infants was 480.25±52.23 µg /100 ml. The mean level of IgG in breast fed infants was 517.59±56.72 µg /100 ml. Conclusions: It is evident from the results of immunoglobulin estimation (Ig A, Ig M and IgG) in infants with artificial milk and in infants with breast milk (vide table 5, 6, 7, 8, 9 and 10) that though the mean serum levels (Ig A, Ig M and IgG) in breast fed infants were slightly higher than that of artificially fed infants. There was no statistically significant difference in the serum immunoglobulin levels between these two groups.